Different radiosensitivity of CD4+CD25+ regulatory T cells and effector T cells to low dose gamma irradiation in vitro - Cao, Mengde; Cabrera, Roniel; Xu, Yiling; Liu, Chen; Nelson, David (International journal of radiation biology, 2011)
Purpose: To determine the radiosensitivity difference of human Cluster of Differentiation (CD)4+CD25+ regulatory T cells (Treg) and effector T cells to low dose gamma ray and elucidate the underlying mechanisms in vitro. Materials and methods: Blood samples were collected from five health subjects and five patients with advanced hepatocellular carcinoma (HCC). Treg and CD4+CD25− T cells were selected using magnetic microbeads. The proliferative profiles, cytokine secretion, and differential expressions of apoptosis-related proteins in Treg and CD4+CD25− T cells were compared using [3H]-thymidine incorporation, Luminex assay and flow cytometry when treated with various low doses of γ-ray. Results: A dose-dependent reduction of proliferation in response to irradiation which paralleled the induction of apoptosis existed in Treg and CD4+CD25− T cells. Treg were more radiosensitive to low-dose irradiation (0.94 Gray [Gy]) than effector T cells. The interferon-γ (IFNγ) was significantly upregulated and interleukin 10 (IL-10) was significantly downregulated in irradiated Treg. An enhanced immune response to low dose gamma ray existed in the peripheral blood in patients with advanced HCC. Higher levels of active caspase-3, CD95, B cell lymphoma 2 (Bcl-2)-associated X protein (Bax) expression were observed in Treg compared to CD4+CD25− T cells. In addition, gamma irradiation activated CD4+CD25− T cells to express CD25. Conclusions: These studies revealed that Treg were more radiosensitive than CD4+CD25− T cells to low dose irradiation. Higher expressions of apoptosis-related proteins such as caspase-3, CD95 and Bax were observed in Treg when compared to CD4+CD25− T cells. Our results suggest that treatment with low doses of gamma irradiation may be a viable strategy to enhance immune response in patients with advanced HCC.